Reasons to use e-cigarettes among adults and youth in the Population Assessment of Tobacco and Health (PATH) study. (June 2019) - Nicksic, Nicole E.; Snell, L. Morgan; Barnes, Andrew J.
Abstract: Background: While e-cigarette use is increasing, reasons to use e-cigarettes are poorly summarized in the literature. The objective of this study was to organize reasons to use e-cigarette items into factors and determine associations between these factors and e-cigarette user characteristics. Methods: Data were drawn from youth (12–17) and adults (18+) in Wave 1 (2013–2014) of the Population Assessment of Tobacco and Health (PATH) study. Exploratory factor analysis was conducted on 13 reasons to use survey items from experimental and established adult e-cigarette users and past 30 day youth e-cigarette users to determine two factors – "alternative to cigarettes" and "larger social environment". Weighted linear regression models tested the associations between e-cigarette user group and sociodemographics and reasons to use factors among youth and adults. Results: Adult current established e-cigarette users were associated with both alternative to cigarettes (β = 0.128, p < .001) and larger social environment (β = 0.063, p < .001) factors, while former established e-cigarette users were associated with alternative to cigarettes (β = 0.064, p < .001). Several adult sociodemographic characteristics were associated with one but not the other factor, or both but in opposite directions. Youth that used e-cigarettes earlier today were also associated with both reasons to use factors (β = 0.127–0.130, p < .01, each); however, youth using any other day in the past 30 days was not associated with either factor. Conclusions: Reasons to use are associated with patterns of e-cigarette use among youth and adults. These factors could support a comprehensive approach to addressing rising e-cigarette use among youth and adults and target certain user populations. Highlights: Two overarching reasons to use e-cigarettes factors were identified. Reasons to use highly motivate adults and youth who use e-cigarettes frequently. Low income and minority adults were associated with "larger social environment". These factors could support policy efforts to target various user groups.